Challenges and Opportunities in Implementing Local Curriculum in Community Schools of Nepal - Sapana Adhikari (Generasi Sains Indonesia, 2024)
Educators and policymakers often face obstacles in adapting and delivering educational content that reflects the community's cultural, environmental and social needs. This study investigates the challenges of implementing local curriculum in community schools of Nepal. The data were collected through documents and interviews with the stakeholders and analyzed through the qualitative content analysis. Key challenges identified include insufficient teacher training, resource limitations, lack of community engagement and inconsistent policy enforcement. Teachers struggle with inadequate instructional materials tailored to local needs, and low community awareness results in limited ownership of the curriculum. Resource disparities and gaps in government support further compound these problems. This study offers insights into improving local curriculum integration in community schools by addressing these challenges. The findings suggest the need for capacity-building, greater community involvement, and more consistent government policies. Ultimately, the local curriculum can enhance culturally relevant education, but its success depends on overcoming these diverse challenges through reforms and sustainable support.